2022
DOI: 10.3389/fgene.2021.708699
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a Novel Ferroptosis-Related Prognostic Model for Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is a clonal malignant proliferative blood disorder with a poor prognosis. Ferroptosis, a novel form of programmed cell death, holds great promise for oncology treatment, and has been demonstrated to interfere with the development of various diseases. A range of genes are involved in regulating ferroptosis and can serve as markers of it. Nevertheless, the prognostic significance of these genes in AML remains poorly understood. Transcriptomic and clinical data for AML patients were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 56 publications
(59 reference statements)
2
28
0
Order By: Relevance
“…Remarkably, it has been reported that AIFM2 protects cancer cells from erastin-, sorafenib-, and RSL3induced ferroptosis via an approach independent of ubiquinol (Bersuker et al, 2019;Doll et al, 2019). Similarly, several studies have shown that AIFM2 represents an unfavorable prognostic factor in prostate cancer, acute myeloid leukemia and uveal melanoma (Luo and Ma, 2021;Lv et al, 2021;Song et al, 2021). However, a recent study has indicated that AIFM2 act as a favorable factor for OS of gastric cancer patients, which is consistent with the findings of our study (Shao et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Remarkably, it has been reported that AIFM2 protects cancer cells from erastin-, sorafenib-, and RSL3induced ferroptosis via an approach independent of ubiquinol (Bersuker et al, 2019;Doll et al, 2019). Similarly, several studies have shown that AIFM2 represents an unfavorable prognostic factor in prostate cancer, acute myeloid leukemia and uveal melanoma (Luo and Ma, 2021;Lv et al, 2021;Song et al, 2021). However, a recent study has indicated that AIFM2 act as a favorable factor for OS of gastric cancer patients, which is consistent with the findings of our study (Shao et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…As a new form of cell death, ferroptosis has demonstrated potential in the treatment of various cancers, including AML ( 18 , 19 ). In fact, researchers have linked ferroptosis-related genes with the prognosis of AML patients and constructed corresponding prognostic models to guide the treatment of AML patients ( 7 , 8 ). However, these findings are biased as the researchers could not confirm whether certain key genes were involved in the regulation of AML ferroptosis in these models.…”
Section: Discussionmentioning
confidence: 99%
“…Leukemia cells are highly sensitive to ferroptosis inducers ( 6 ); therefore, ferroptosis may be closely related to the development of leukemia. Researchers have constructed corresponding prognostic prediction models based on the expression levels of ferroptosis-related genes in AML patients, which are available in public databases ( 7 , 8 ), to identify potential therapeutic targets and mechanisms. Then, the corresponding predictive model needs further experimental studies to confirm whether some key genes in the model are involved in the regulation of ferroptosis in AML.…”
Section: Introductionmentioning
confidence: 99%
“…To compare differentially expressed genes (IFR-DEG) associated with immune ferropotosis in STAD, TCGA database was used for subsequent analysis. The downloading of human immune-related genes (IRGs) from the ImmPort database ( ) and the GeneCard database ( ) reached 17,500 in total, and the downloading of ferropotosis-related genes (FRGs) from the FerrDb database ( ) and previous literature ( 18 ) reached 398 in total. The cutoff condition settings are log2 fold change (logFC) < -2, p -value < 0.05, which is statistically evident.…”
Section: Methodsmentioning
confidence: 99%